2019
DOI: 10.1111/jocd.12911
|View full text |Cite
|
Sign up to set email alerts
|

Role of broad‐spectrum sunscreen alone in the improvement of melasma area severity index (MASI) and Melasma Quality of Life Index in melasma

Abstract: Background Sunscreens have long been an indispensable part in treating melasma as ancillary agents. None of previous studies have evaluated the role of sunscreens alone in the improvement of melasma. Aims Our objective was to study the role of broad‐spectrum sunscreen with sun protection factor 19 and PA+++ as the sole agent for improvement of melasma. Methods A total of 100 patients with melasma were included in the study. Following proper method of application of 3 mL sunscreen, thrice daily, Melasma Area Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 16 publications
2
32
0
5
Order By: Relevance
“…17 A recent study showed that 100 participants were required to apply sunscreen (Garnier White Complete ® SPF19 PA+++) during the daytime every 3 hours (approximate 3 mL each time) and found that modified Melasma Area Severity Index (mMASI) score, Hi-MELASQOL score decline, and mMASI score was marginally associated with Hi-MELASQOL score after 12 consecutive weeks of treatment. 18 This study confirmed that use of sunscreen alone can improve the skin lesions and the quality of life of patients with melasma. In one study by Lakhdar et al, 19 the researchers have found that the clinical improvement was observed in 8 out of 12 volunteers who were affected by a pre-existing melasma and regular application of sunscreen in 185 pregnant women could prevent melasma and only five new cases of melasma occurred.…”
Section: Sunscreen Productssupporting
confidence: 76%
“…17 A recent study showed that 100 participants were required to apply sunscreen (Garnier White Complete ® SPF19 PA+++) during the daytime every 3 hours (approximate 3 mL each time) and found that modified Melasma Area Severity Index (mMASI) score, Hi-MELASQOL score decline, and mMASI score was marginally associated with Hi-MELASQOL score after 12 consecutive weeks of treatment. 18 This study confirmed that use of sunscreen alone can improve the skin lesions and the quality of life of patients with melasma. In one study by Lakhdar et al, 19 the researchers have found that the clinical improvement was observed in 8 out of 12 volunteers who were affected by a pre-existing melasma and regular application of sunscreen in 185 pregnant women could prevent melasma and only five new cases of melasma occurred.…”
Section: Sunscreen Productssupporting
confidence: 76%
“…This result indicated that ITR has an inhibitory effect on melanogenesis in melasma. The improvement of mMASI scores in HA group would rather come from the adequate photoprotection and the regular use of sunscreen as previous study by Sarkar et al 30 Their research demonstrated the improvement of melasma by reduction of MASI score and significantly improved quality of life of melasma patients after using sunscreen alone for 12 weeks 30 . Although HA might not have a direct effect on melanogenesis, it could improve skin quality, provide antioxidative effect, enhance dispersion of melanin pigment, and accelerate epidermal desquamation as the previous clinical study by Ibrahim et al 20 They found that the combination of hydroquinone, glycolic acid, and HA showed greater efficacy than hydroquinone and glycolic acid in the treatment of melasma.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies that aimed to explore the treatment of melasma reported a statistically significant decrease in MELASQoL scores after treatment, despite the varied intervention methods [ 31 36 ]. Sarkar et al found that MELASQoL scores decreased (from 47.27 to 37.93) after 12 weeks of sunscreen use, which suggested that sunscreen use subjectively improved the quality of life of patients with melasma [ 37 ]. Thus, interventions that effectively treat melasma can improve the quality of life.…”
Section: Discussionmentioning
confidence: 99%